A Multi‐Factor Account of Degrees of Awareness. (10th April 2017) - Fazekas, Peter; Overgaard, Morten
Abstract: In this paper we argue that awareness comes in degrees, and we propose a novel multi‐factor account that spans both subjective experiences and perceptual representations. At the subjective level, we argue that conscious experiences can be degraded by being fragmented, less salient, too generic, or flash‐like. At the representational level, we identify corresponding features of perceptual representations—their availability for working memory, intensity, precision, and stability—and argue that the mechanisms that affect these features are what ultimately modulate the degree of awareness. We conclude the paper by demonstrating why the original interpretations of certain empirical findings that apparently pose problems for our account are, in fact, flawed.